2000
DOI: 10.4049/jimmunol.164.11.5877
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CD40-CD154 Interaction in Antiviral T Cell-Independent IgG Responses

Abstract: Polyomavirus (PyV) infection elicits protective T cell-independent (TI) IgG responses in T cell-deficient mice. The question addressed in this report is whether CD40 signaling plays a role in this TI antiviral IgG response. Because CD40 ligand (CD40L) can be expressed on numerous cell types in addition to activated T cells, it is possible that cells other than T cells provide CD40L to signal through CD40 on B cells and hence positively influence the antiviral TI IgG responses. In this study we show, by blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…3F), which can be stimulated by CD40L, classically on the surface of Th cells. Significantly, CD40L on the surface of adjacent B cells may provide functional activation of CD40 in Th cell-independent responses (44). Paracrine or autocrine signaling by MIP-1␣, IFN-␣, and IL-6 may regulate the Ab isotypes induced by HPV16 VLP and are consistent with a defense response (35,63,64).…”
Section: Discussionmentioning
confidence: 92%
“…3F), which can be stimulated by CD40L, classically on the surface of Th cells. Significantly, CD40L on the surface of adjacent B cells may provide functional activation of CD40 in Th cell-independent responses (44). Paracrine or autocrine signaling by MIP-1␣, IFN-␣, and IL-6 may regulate the Ab isotypes induced by HPV16 VLP and are consistent with a defense response (35,63,64).…”
Section: Discussionmentioning
confidence: 92%
“…We previously showed that SCID mice reconstituted with T cell-depleted wild-type splenocytes generated VP1-specific TI IgM and IgG Ab responses after infection with PyV (20). We therefore reconstituted SCID mice with either unfractionated or T cell-depleted wild-type or MyD88 KO splenocytes and measured VP1-specific IgM and IgG Ab responses after PyV infection.…”
Section: Initiation Of Acute Td Responses To Pyv In the Absence Of Mymentioning
confidence: 99%
“…VP1-specific ELISAs were conducted as previously described (20). Briefly, purified recombinant VP1 protein (0.1 g/ml in carbonate buffer) was used as an immunoadsorbant.…”
Section: Vp1-specific Elisamentioning
confidence: 99%
“…However, it has also been described that a blocking anti-CD40L Ab (MR1) had little or only modest effect on the antiphosphorylcholine response and that CD40 Ϫ/Ϫ dendritic cells elicited an anti-phosphorylcholine response that was comparable to that observed for wild-type dendritic cells (19). Szomolanyi-Tsuda et al (20) stressed the role of the CD40-CD154 interaction in anti-polyoma virus thymus cell-independent IgG responses. Finally, it has been described 1) that neutralization of CD40L reduced the Ab response to pneumococcal caps-PS elicited by immunization with whole bacteria or with a caps-PS-protein conjugate and 2) that the immune response to a caps-PS-protein conjugate was higher in wild-type mice than in CD40L-deficient mice (21,22).…”
mentioning
confidence: 99%